The Implementation Of Lean Manufacturing and Industrial Technology 4.0 On Business Performance - Siti Maemunah (Publikasi Indonesia, 2021)
The problem of this reasearch has entered the industrial revolution 4.0 (4IR), then strategy implementation need to be done through 4IR road map. Specific aspect which has effect to Industry 4.0 Technology Adoption are technology intensity, strict capital & human resources investment, therefore performances measurement which consider whole organization become more relevant. The purpose of this research was to test moderation effect of Industry 4.0 Technology process-related and product/service-related into the lean manufacturing implementation to business performance. The methodology of this research is using PLS-SEM approach with SMART-PLS software. Measurement of variable datas were obtained through 1 -5 Likert scale survey which was distributed to PT.XYZ employee. The finding of this research show those Industry 4.0 Technology process-related and product/servicerelated were not moderating implementation of lean manufacturing to business performance in PT. XYZ. The limitation in this study were only for PT. XYZ operational scope and were using data from Aug – Nov 2020. Conclusion of this research can not be generalized to other research object or to describe PT. XYZ in another time.